The Influence of Teaching Material Distribution Costs and Services on Student Satisfaction in Universitas Terbuka UPBJJ Majene - Syahrinullah (Formosa Journal of Multidisciplinary Research, 2024)
In providing services owned by the Open University, it is necessary to guarantee good quality services in terms of tuition fees the quality of service, and distribution of teaching materials that can reach all students. It is hoped that with more affordable education costs and fast-quality teaching material distribution services, the level of student satisfaction as customers can be maximized. This research uses a quantitative approach. The analysis method uses multiple regression analysis techniques. The research results found that costs had a significant influence on student satisfaction, teaching material services had a significant influence on student satisfaction, and simultaneously the variable costs and teaching material distribution services had a significant influence on student satisfaction at the UPBJJ Majene Open University.